The Impact of Nutritional Education on Diabetes Outcomes in Inpatient Settings - Fadel, Duaa Mohammed; Aljomaie, Hassan Abdulrahman H; Alhazmi, Saud Ali; Alkhyfi, Halah Ahmed (Journal of Posthumanism, 2024)
Diabetes Mellitus (DM) is a chronic metabolic disease which can lead to various complications such as cardiovascular disease, nephropathy, and neuropathy. It is expected to affect 592 million by 2035. Nutritional education and therapy have gained importance in recent years besides antidiabetic drugs. Individuals with diabetes should be referred to a registered dietician to receive diabetes nutrition education once the diagnosis is confirmed. Diabetic patients experience higher hospitalization rates for both diabetes-related and unrelated conditions, as well as increased 30-day readmission rates compared to those without diabetes. Hospital stays offer a valuable opportunity not only for accurate diagnosis and treatment but also for delivering self-management education to diabetic patients. However, evidence evaluating the role of nutritional education in inpatient diabetes patients is rare. The aim of this review is to explore current evidence focusing on the impact of nutritional education on diabetes outcomes in inpatient settings. Studies showed that nutritional education significantly reduces fasting blood sugar levels, glycated hemoglobin HbA1c, BMI, and the risk of microvascular complications and cardiovascular disease. Different models for providing inpatient diabetes education have been introduced, each with different frameworks and effects. These models can be classified into diabetes non-specialty care education models, diabetes-specialty diabetes care models and technology-enabled education models. Interdisciplinary diabetes care model and the Chronic Illness Management Program are examples of inpatient diabetes education models that included nutritional education; however, these models showed debatable results. Most existing research either focuses on outpatient nutritional education or on general inpatient diabetes education without addressing the distinct role of nutrition. Further research is needed to explore and validate the effectiveness of inpatient diabetes nutritional education.